Hygroscopic stresses in asymmetric biocomposite laminates submitted to various relative humidity conditions. (July 2020) - Péron, Mael; Célino, Amandine; Jacquemin, Frédéric; Le Duigou, Antoine
Abstract: Hygroscopicity of natural fibers influences biocomposites lifetime submitted to wet environments. The present study investigates the hygroscopic stresses state in a flax fiber reinforced polypropylene composite when submitted to different environmental conditions from the dried state through various relative humiditiy (RH) to immersion. An experimental and modelling strategy is applied on asymmetric biocomposites to estimate the stresses distribution through their thickness. On dry condition, transverse tensile stresses reached 26.4 MPa. These stresses were nullified at 50%RH and then increased again until 90%RH or immersion conditions are applied. The evolution of the internal stresses influence drastically the tensile strength of biocomposites. Indeed, the internal stresses overcome the transverse strength of Flax/MAPP unidirectional ply, which potentially leads to damage. Environmental loading and gradient effect also drastically influence the internal stresses. A progressive humidification step enables to reduce drastically the stresses intensity with levels lower than 10 MPa thanks to lower hygroscopic gradients.